Quantitative analysis of FJ 194940.1 gene expression in colon cancer and its association with clinicopathological parameters - Bartczak-Tomczyk, Malwina; Sałagacka, Aleksandra; Mirowski, Marek; Jeleń, Agnieszka; Balcerczak, Ewa (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: The FJ 194940.1 gene is located on chromosome 1 and consists of 6 exons and 5 introns. The gene undergoes alternative splicing and its isoforms appear during cancer development. Evidence suggests that expression of FJ 194940.1 splice variants relate to colorectal cancer progression. This paper discusses the quantitative analysis of the exon V expression level of FJ 194940.1 in colon cancer. The aim of the study is to carry out quantitative analysis by real-time PCR in a series of 102 colon cancer samples that had previously shown presence of exon V expression. To compare the exon V expression level with certain histological parameters and clinical staging of the neoplasm in order to assess its potential role as a prognostic factor in colon cancer. Material and methods: Tissue specimens of colorectal cancer were obtained from the Oncological Centre of Lodz, Poland.Total RNA isolation was performed in accordance with the protocol enclosed in the Total RNA Prep Plus Minicolumn Kit (A&A Biotechnology, Poland). Reverse Transcriptase-PCR reaction was carried out using Enhanced Avian HSRT-PCR Kit, Sigma, according to the manufacturer’s protocol.. Presence of cDNA in each sample was checked by PCR amplification of β-actin . Only samples showing the PCR product of this housekeeping gene were included in further tests. The amount of FJ 194940.1 transcript containing exon V was analysed by means of real-time PCR. Results : Exon V expression level is not significantly related to any clinicopathological features in colon cancer. However, there was a tendency towards a lower exon V expression level in a group of cases where vessel invasion was present (p = 0.0697). Additionally, the risk of death in patients with a low exon V expression level was more than two times higher when compared to patients with a high exon V expression level. Conclusions : FJ 194940.1 gene expression correlates with cancer progression independently of analysed clinicopathological parameters.